1985
DOI: 10.1073/pnas.82.15.5040
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the soybean nodulin-35 gene encoding uricase II localized in the peroxisomes of uninfected cells of nodules

Abstract: , a subunit of nodule-specific uricase (uricase II) of soybean (Glycine max), is shown to be preferentially synthesized on free polysomes during nodule development and is localized in peroxisomes of the uninfected cells of this tissue. A cDNA clone, isolated by using mRNA from immunoprecipitated polysomes, revealed the primary structure of this protein with a molecular mass of 35,100. That this clone represents N-35 was confirmed by comparing the deduced amino acid sequence with the partial sequence of a CNBr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
2

Year Published

1985
1985
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(84 citation statements)
references
References 39 publications
1
81
0
2
Order By: Relevance
“…We did not detect extensive regions of amino acid sequence similarity between isocitrate lyase and other plant peroxisomal proteins, i.e. malate synthase (Comai et al, 1989), soybean uricase (Nguyen et al, 1985), and spinach glycolate oxidase (Volokita and Somerville, 1987). However, we note that the carboxyterminal three amino acids (Ser-Arg-Met) of isocitrate lyase are similar to those implicated to be both necessary and sufficient to target other proteins to peroxisomes (Ser-Lys/ His-Leu; Gould et al, 1988).…”
Section: Identification and Structure Of Isocitrate Lyase Cdna Clonesmentioning
confidence: 99%
“…We did not detect extensive regions of amino acid sequence similarity between isocitrate lyase and other plant peroxisomal proteins, i.e. malate synthase (Comai et al, 1989), soybean uricase (Nguyen et al, 1985), and spinach glycolate oxidase (Volokita and Somerville, 1987). However, we note that the carboxyterminal three amino acids (Ser-Arg-Met) of isocitrate lyase are similar to those implicated to be both necessary and sufficient to target other proteins to peroxisomes (Ser-Lys/ His-Leu; Gould et al, 1988).…”
Section: Identification and Structure Of Isocitrate Lyase Cdna Clonesmentioning
confidence: 99%
“…In (14). cDNA probes for Northern hybridization were prepared by nick-translation as described (12).…”
Section: Methodsmentioning
confidence: 99%
“…A 35,000 mol wt subunit of soybean root-nodule uricase (nodulin-35) has been purified to homogeneity; this enzyme has been 'Supported in part from Consejo Nacional shown to differ in physicochemical properties and to have no antigenic cross-reactivity with the enzyme found in uninfected roots or leaves (2). cDNA and genomic clones encoding for uricase II have been isolated and the deduced primary structure of the enzyme from DNA sequence has been reported (14). The lack of cross-hybridization of nodulin-35 (N-35) cDNA with RNAs from other tissues indicated that N-35 is a nodule-specific gene product which is induced only during the Rhizobiumsoybean symbiosis.…”
mentioning
confidence: 99%
“…Xanthine dehydrogenase is associated with discrete organelles and present exclusively in uninfected cells as demonstrated by Nguyen (20), while Triplett (28) found xanthine dehydrogenase activity in the infected cells. Uricase is present in peroxisomes in uninfected cells (21). In sucrose density gradient studies allantoinase was demonstrated to be associated with the microsomal fraction (11).…”
mentioning
confidence: 99%